2015
DOI: 10.1590/0103-9016-2014-0136
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and evapotranspiration of melon grown with plastic mulch in the Brazilian semiarid region

Abstract: Methods for obtaining evapotranspiration based on energy balance are potentially interesting for analyzing the impact of crop management practices on energy fluxes and, thus, the loss of water from the plant surface. Among the methods for estimating ET based on energy balance, the Bowen Ratio Energy Balance (BREB) has been well evaluated and is recommended by several authors for different crops (Irmak, et al., 2013;Hou et al., 2010;Zhang et al., 2010;Zeggaf et al., 2008).This study applied the BREB method to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
1
9
2
4
Order By: Relevance
“…The agreement between the λE/Rn and LAI curves were also observed in cotton crops at oasis Shihezi in northern Xinjing, China (Zhou et al 2012). Compared with other studies in muskmelon crop, such as Borges et al (2015), Mossoró region, Brazilian Semi-Arid, it appears that the portions of Rn converted into λE found in this study were lower. Borges et al (2015) reported that during Mid-season λE values corresponding to almost all available energy, reaching values higher than net radiation during the daytime.…”
Section: Resultscontrasting
confidence: 96%
See 3 more Smart Citations
“…The agreement between the λE/Rn and LAI curves were also observed in cotton crops at oasis Shihezi in northern Xinjing, China (Zhou et al 2012). Compared with other studies in muskmelon crop, such as Borges et al (2015), Mossoró region, Brazilian Semi-Arid, it appears that the portions of Rn converted into λE found in this study were lower. Borges et al (2015) reported that during Mid-season λE values corresponding to almost all available energy, reaching values higher than net radiation during the daytime.…”
Section: Resultscontrasting
confidence: 96%
“…Compared with other studies in muskmelon crop, such as Borges et al (2015), Mossoró region, Brazilian Semi-Arid, it appears that the portions of Rn converted into λE found in this study were lower. Borges et al (2015) reported that during Mid-season λE values corresponding to almost all available energy, reaching values higher than net radiation during the daytime. During late season Borges et al (2015) found λE values ranging from 77 to 89% of the available energy (Rn), while those found in this study ranged from 62 to 71%.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…All sites were characterized as being hyperxerophilic savanna with strong human pressure, so antropic degradation was common to all plants habitats. According to Koppen, the climate classification of the region is BSwh (very hot and dry, with rainfall in the summer and early autumn), with an average temperature of 27.2 °C, total annual rainfall of 766 mm and average relative humidity of 69 % (BORGES et al, 2015). Fruits were collected when they were fully ripened on the plant.…”
Section: Methodsmentioning
confidence: 99%